Circumcising "Revelation-Based" Thinking? On the Rationality of Inter-religious Dialogue in the Encounter between Jews and Christians - Fehige, Joerg H. Y. (Toronto journal of theology, 2013)
This paper provides a continuation of my analysis of the powers and perils of what I call dialogical rationality with respect to the encounter between Jews and Christians. Its primary aim is to define the relationship between dialogical and philosophical rationality with respect to the encounter between Judaism and Christianity. First I introduce the basic principles of dialogical rationality that I developed elsewhere. In a second step one of these principles is scrutinized in the form of a meta-philosophical discussion. At its centre lies the question of whether philosophy of religion should be detached from biblical faith (and thus from divine revelation) to be of use in any justifications of inter-religious dialogue between Jews and Christians. The main reference point of my discussion is recent work on the state of analytic philosophy of religion. I argue that there is no reason to be critical of philosophy's contributions to justifications of inter-religious dialogue between Jews and Christians.